Diet, nutrition, and cancer (National Academy Press, 1982)
Based on a review of the scientific evidence, this book provides the assessment yet of the relationship between dietary and nutritional factors and the incidence of cancer. It presents dietary guidelines that are likely to reduce the risk of cancer as well as ensure good nutrition.